The influence of hydrogen plasma pre-treatment on the structure of BDND electrode surface applied for phenol detection - Azevedo, Adriana Faria; Souza, F. A.; Hammer, Peter [UNESP]; Baldan, M. R.; Ferreira, N. G. (Springer, 2011)
The surface properties of boron-doped nanocrystalline diamond films treated with H(2) plasma was investigated in regard to their electrochemical response for phenol oxidation. The surface of these films is relatively flat formed by crystallites with sizes of about 40 nm. X-ray photoelectron spectroscopy analyses showed that electrode surface has a high amount of C-H bonds. This behavior is in agreement with Mott-Schottky plot measurements concerning the flat band potential that presented a value as expected for hydrogenated diamond surface. This electrode presented the phenol detection limit of 0.08 mg L(-1) for low phenol concentrations from 40 to 250 mu mol L(-1).
Keywords: Nanocrystalline diamond films; Boron doping; Phenol oxidation; Electrochemistry; X-ray photoelectron spectroscopy